Influence of Tax Planning and Earnings Management on the Financial Health of Companies Listed on The Stock Exchange of Thailand - Chumaungphan, Orawon; Wannalo, Woralak; Boonyarasai, Phathamon (Rajapark Journal, 2024)
This research aims to analyze the influence of tax planning and earning management on financial health, which includes: financial liquidity, operating efficiency, and financial policy of companies listed on the Stock Exchange of Thailand. By collecting data from Form 56-1 on the website of the Stock Exchange of Thailand from 2018–2022, a total of 327 companies were analyzed by multiple regression analysis. From the study, it was found that tax planning (measured by the ratio of tax expenses to total assets) has a positive influence on financial health, (measured by financial liquidity and operating efficiency) and a negative influence on earning management. It was also found that tax planning (measured by the ratio of tax expenses to net cash flow from operating activities) has a positive influence on financial health (measured by financial policy).